Exact model knowledge and direct adaptive controllers on ball and beam - Turker, Turker; Gorgun, Haluk; Zergeroglu, Erkan; Cansever, Galip (IEEE, 2007)
This paper presents analysis and implementation of Exact Model Knowledge (EMK) and Direct Adaptive control schemes on the 4th order ball and beam system in which the dynamics of the ball position and the dynamics of the beam angle are cascaded. For the controller analysis the error dynamic equations for ball position and the beam angle are derived for both cases. Following, experimental studies are conducted based on the proposed control approaches and it is presented that constant and sinusoidal references for the ball position are tracked asymptotically.
Keywords: Automation & Control Systems; Engineering